Pengaruh Kebijakan Hutang (Debt) dan Return On Asset (ROA) terhadap Kebijakan Dividen (Studi pada Perusahaan Consumer Goods Periode 2015-2017) - Zaenul Muttaqien (JMK (Jurnal Manajemen dan Kewirausahaan), 2019)
This research was conducted to examine the effect of Debt Policy (DEBT) and Return On Assetss (ROA) variables on Dividend Payout Ratio (DPR) in Consumer Goods.The sampling technique used was purposive sampling method with the criteria (1). listed on the Indonesia Stock Exchange during the 2015-2017 research period; (2). Distributing cash dividends for three consecutive years during the 2015-2017 research period; (3). Have complete financial report data on Debt Policy (DAR) and Return On Assetss (ROA) during the study period, namely in the years 2015-2017. A sample of 14 companies from 40 companies was obtained. The analysis technique used is a multiple linear regression model with hypothesis testing that is F test to determine the effect simultaneously and t test to determine the effect partially with a significance level of 5%.